Integrasi Database untuk Visualisasi dan Laporan pada Divisi Humas Universitas Swasta di Surabaya - Setiawan, Nico (Jurnal Titra, 2019)
For a university, promotional activities to introduce study programs at the university to high school students are one way to get new students. This private university in Surabaya (USS) was also done. Providing information about USS was conducted in high schools, both on Java and outside Java, through educational exhibitions. USS Public Relations requires a team or division that handles this. At present, the promotion division is carried out by the public relations department. Public Relations formed a team consisting of several lecturer staff and students who will be assigned to the intended places. Activities to be carried out are recorded in a financial report that is not connected to the database. The problem is that there is no database used so the report is done manually and takes a long time. The current report only records the amount of expenditure without providing any other information and the preparation of the financial statements while running is still not neat. The database helps PR in preparing financial reports so they do not work several times in compiling reports that are certain and save the time needed. The system will also be able to visualize data from the financial statements in showing the magnitude of the costs incurred by public relations in promotional activities carried out based on each school.